The Islamic Navy in the Era of the Rightly- Guided Caliphs - Nikrish, Ismail Hasan (Journal of Humanities & Social Sciences, 2022)
The peoples of the Mediterranean knew the sea, and they dominated the world navy at the time, each according to his capabilities, such as Greece, Carthage, the Romans, and the Persians in the Indian Ocean, and the Arabs are like these peoples, since the sea surrounds their homeland from all sides. Despite their knowledge of the sea and its horrors, they are in direct contact with the sea and its peoples, but the inhabitants of the middle of the Arabian Peninsula did not like to ride the sea. The Islamic Navy began modestly with simple attempts, which began since the entry of southern Arab elements on the scene of Islamic military events. Oman and Yemen contributed to the Islamic conquests of peace through the involvement of their sons in the ranks of the Islamic army. Caliph Omar Ibn Al- Khattab, may God be pleased with him, opposed going to the sea, so he did not allow Muawiyah Ibn Abi Sufyan to go into the sea, and he went beyond that by removing Al- Ala Ibn Al- Hadhrami from his position as governor of Bahrain after his invasion of the Persians on the Indian coast. This policy of Umar, may God be pleased with him, explains that at this stage he intends to wait for the conquests until the Muslims can gain control of the conquered lands, just as the land conquests have not ended yet, and the naval expertise needs more training and anchors. Since the era of Caliph Othman bin Affan, may God be pleased with him, the naval conquests began, and the Islamic state had its distinguished fleet, and Muslims were trained to ride the sea.